The Critic and the Cure - Amanda Malerba; Andreas Hetzel (Critical Hermeneutics)
This article aims to analyze Hannah Arendt's critique of psychoanalysis in her short essay published in 1943, We refugees, in which, in the midst of her reflections on the changing social situations of Jewish refugees from the Second World War. Arendt describes psychoanalysis as an outmoded practice of a tedious elite who tell “ghost stories” based on minor events from their childhoods, which, in her perception, becomes unnecessary after the frightening events witnessed during the war. This critique in itself could already serve as an object of detailed analysis, nevertheless it becomes particularly interesting when, in the following paragraphs, Arendt proceeds to examine the suicides committed by Jewish refugees, who are supposed to be safe from the dangers of war in the countries where they are welcomed, basing her investigations on possible internal factors. This approach is very similar to Sigmund Freud's so-called social theory, describing a series of symptoms which, although they only affect individuals, have a social origin, that is, they are due to historical moments or events that individuals all together experience. Arendt discusses her suspicion of the optimism with which many Jews faced the loss of their mother tongue, the sense of feeling like victims who had to be saved and the necessity of adapting to the new habits of their new countries' cultures – whereas all of these themes are the subject of psychoanalytic studies. Lastly, the author describes an individual who would illustrate her concerns about Jewish optimism and the constant pursuit of being part of the national culture and identity: Mr. Cohn, who would become one of the most famous characters in Arendtian thought, which, in this sense, can also be compared to a clinical case, presented in psychoanalytic writing to illustrate the development of symptoms and the analysis. Despite ironizing psychoanalytic practice, the following pages will analyse whether it is possible to relate Arendt's investigation into the suicides of Jewish refugees and the fragile state in which refugees find themselves in the countries that receive them to the psychoanalytic methods criticized by the author in the same essay.